Los fungicidas sistémicos en la prevención y control de la roya del cafeto hemileia vastatrix berk. & br en el cantón Piñas provincia de El Oro - Feijóo Galarza, Jaime Alcivar (2014)
This research was conducted in the San Pedro site, Parroquia Piñas, Cantón Piñas, property of Flavio Ochoa, between March and august/2014, in which the there was raised “Systemic fungicides in the prevention and control of coffee roya (Hemileia vastatrix Berk. & Br.)", with the following objectives: To determine the optimal dosage of systemic fungicides tested in the essay to control coffee roya; 2. To compare the severity and incidence of coffee roya treatment. The experimental design was randomized blocks, consisting of 10 treatments with 3 replicates each, totaling 30 experimental units, consisting of 40 coffee trees. For the treatments three systemic fungicides, three doses were used: low, medium and high; Nomad: 300-400-500 cc/ha; Alto 100: 150-250-350 cc/ha; Amistar Top: 400-500-600 cc/ha. The variables evaluated were: Incidence, severity, and productive efficiency Abbott variables. 2 applications of treatments at 0 and 45 days were made.   In each experimental unit 10 plants were selected, which were divided into three strata: high, medium and low incidence in these plants (upper stratum, medium and low) and severity (5 plants, middle layer) was evaluated. The incidence was assessed at 0, 30, 60, 90, 120 and 150 days and the severity is at 0, 30 and 60 days. Following the investigation it was determined that the progressive increase in the control condition was very severe with an average incidence of 0.49% / day. In terms of control, efficiency and effectiveness of the treatments at 150 days, it was determined that the T3 proved to be the best treatment for roya control in the study area.   The results have revealed at the timely application of fungicides is a key activity of the integrated management of coffee roya.